A Best Proximity Point Result in Modular Spaces with the Fatou Property - Mohamed Jleli; Erdal Karapınar; Bessem Samet (Abstract and Applied Analysis)
Consider a nonself-mapping , where is a pair of nonempty subsets of a modular space . A best proximity point of is a point satisfying the condition: . In this paper, we introduce the class of proximal quasicontraction nonself-mappings in modular spaces with the Fatou property. For such mappings, we provide sufficient conditions assuring the existence and uniqueness of best proximity points.